Non-Combustible Nicotine Use Among Amateur and University Athletes: Prevalence, Patterns and Reasons—A Scoping Review - Nguyen Hoang; Melis Selamoglu; Isabella Papadopoulos; Chi Lao; Holly Wild; Susan Kotwas; Ines Rio; Kim Turudia; Dale Cridland; Chris Barton (International Journal of Environmental Research and Public Health, 2026)
Background: Nicotine exposure is increasingly occurring through non-combustible products such as electronic cigarettes and nicotine pouches. Although sport participation is often considered protective against substance use, nicotine use appears to be increasingly normalised within performance-oriented sporting environments. Methods: This scoping review synthesised evidence on non-combustible nicotine use among amateur and university athletes. Following Joanna Briggs Institute (JBI) methodology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines, the searches were conducted in Ovid MEDLINE, Web of Science, Embase, Scopus, SPORTDiscus, and CINAHL for peer-reviewed studies published from 2019 onwards that examined non-combustible nicotine use in these populations. Results: Eleven studies, predominantly cross-sectional and conducted in high-income Western countries, met the inclusion criteria. Nicotine use was more common among male athletes, younger athletes, and those participating in team and contact sports, particularly for e-cigarette use. Across studies, nicotine use was frequently characterised as socially normative and compatible with sport, influenced by peer networks, social identity, perceived harm reduction, and beliefs regarding performance enhancement, coping, and recovery. The evidence base was limited by inconsistent measurement approaches and a predominance of studies examining demographic correlates rather than behavioural drivers. Conclusions: Non-combustible nicotine use appears embedded within sport-specific social norms and performance-related beliefs, highlighting the need for theoretically informed research and sport-specific prevention strategies.